OMAH RAJUT ASA - Dessyanna Natalie; Sidhi Wiguna Teh (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
School of Therapy for Autistic Children is an educational institution ranging from kindergarten (TK), elementary school (SD), junior high school (SMP), and senior high school (SMA) in Jakarta which is devoted to Children with Autism. The background underlying this design is because educational facilities for children with autism  are classified as inadequate and have not been able to meet all the educational needs for sufferers so that they can develop their talents and potential, and obtain education that is equivalent to normal children their age. In fact, these children are considered to have no talent and potential that can be developed. Most of the general public has a negative perspective on children with autism. As a result, there are so many children with autism who have talents and potentials that, if developed, can far exceed what normal children have in general. In planning and designing this Special School, it will be interpreted through the concepts of architectural and behavioral psychology.  Keywords: Autism, Psychology of Architecture, Jakarta. AbstrakSekolah Terapi Anak Autis Merupakan sebuah lembaga pendidikan mulai dari taman kanak - kanak (TK), tingkat sekolah dasar (SD), sekolah menengah pertama (SMP), dan sekolah menengah atas (SMA) di Jakarta yang dikhususkan bagi Anak Penyandang Autisme. Latar belakang yang melandasi perancangan ini yaitu karena fasilitas pendidikan bagi anak autis tergolong belum memadai dan belum dapat memenuhi segala kebutuhan pendidikan bagi penderita agar mereka dapat mengembangkan bakat dan potensi diri, serta memperoleh pendidikan yang setara dengan anak normal seusianya. Faktanya, anak- anak ini dianggap tidak memiliki bakat dan potensi yang dapat dikembangkan. Kebanyakan masyarakat umum memiliki perspektif negatif mengenai anak penyandang autisme. Hasilnya, terdapat begitu banyak anak penyandang autisme yang memiliki bakat dan potensi diri yang apabila dikembangkan, dapat jauh melebihi apa yang dimiliki anak normal pada umumnya. Dalam perencanaan dan perancangan Sekolah Luar Biasa ini akan diinterpretasikan melalui konsep Psikologi arsitektur dan perilaku.